2018
DOI: 10.1111/cei.13191
|View full text |Cite
|
Sign up to set email alerts
|

Increased β2-adrenoceptor phosphorylation in airway smooth muscle in severe asthma: possible role of mast cell-derived growth factors

Abstract: The purpose of this study was to investigate whether growth factors produced by activated human lung mast cells (HLMCs) impair β -adrenoceptor (β -AR) function in human airway smooth muscle (ASM) cells. Protein array analysis confirmed the presence of various growth factors, including transforming growth factor (TGF)-β1, in the supernatants of high-affinity IgE receptor (FcεRI)-activated HLMCs which, when applied to ASM cells, impaired albuterol-induced cyclic adenosine monophosphate (cAMP) production, an effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
(41 reference statements)
0
14
1
Order By: Relevance
“…3, we show that TGF-β1 attenuates, rather than augments, grk2 and grk3 expression. Despite our previous findings showing that β 2 AR phosphorylation is increased following TGF-β1 exposure [26], we determined that the increase in TGF-β1induced β 2 AR phosphorylation is not due to increased expression of GRK2/3.…”
Section: Tgf-β1 Attenuates Grk2 and Grk3 Expression In Hasmcontrasting
confidence: 85%
See 2 more Smart Citations
“…3, we show that TGF-β1 attenuates, rather than augments, grk2 and grk3 expression. Despite our previous findings showing that β 2 AR phosphorylation is increased following TGF-β1 exposure [26], we determined that the increase in TGF-β1induced β 2 AR phosphorylation is not due to increased expression of GRK2/3.…”
Section: Tgf-β1 Attenuates Grk2 and Grk3 Expression In Hasmcontrasting
confidence: 85%
“…Despite this limitation, we have shown effects of TGF-β1 on HASM to be recapitulated in small airways derived from human lungs [10]. Additionally, while it would be interesting to study this phenomenon in asthma-derived HASM, we and others have demonstrated that β 2 -agonist-induced cAMP production in these cells is already blunted due partially to increased PDE expression [26,38]. Therefore, exposure of asthma-derived HASM to TGF-β1 will likely have little effect on modulating β 2 -agonist-induced cAMP production.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, some studies report that this neuronal regulation is modified by immune cells. Mast cells infiltrate in airway smooth muscles of patients with asthma (68), and mast cell-derived TGF-β induces phosphorylation of β2AR on smooth muscle cells, which results in a reduced response to a β2AR agonist (69). In addition, noradrenaline can directly suppress proinflammatory cytokine production from immune cells through β2AR, and β2AR-deficient mice have more severe type 2 airway inflammation in allergen-nonspecific asthma mouse models.…”
Section: Figure 1 the Interaction Between Sensory Neurons And Immunementioning
confidence: 99%
“…Infiltration of mast cells has been described within the epithelium, submucosa layer and airway smooth muscle and has been shown to correlate with disease severity [reviewed in ( 3 )]. Bidirectional interactions between human lung mast cells, and structural airway tissues have been demonstrated using a co-culture model system with mast cells being able to drive pro-asthmatic responses in airway smooth muscle (ASM) cells including loss of β2-adrenoceptor function indirectly via the paracrine action of secreted TGFβ ( 4 ), or following direct cell-cell physical interaction ( 5 , 6 ). Similarly, β2-adrenoceptor dysfunction can also be observed in human lung mast cells as a result of the autocrine action of secreted SCF ( 5 , 7 ).…”
Section: Introductionmentioning
confidence: 99%